Importance of variety meat utilization to the meat industry. (1st October 2017) - Schaefer, Dan; Arp, Travis
Abstract: Variety meats add considerable value to the red meat and poultry industries Exports play a key role in variety meat utilization Variety meats are used in a multitude of culinary applications across cultures